2018
DOI: 10.1002/biof.1439
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein, its effects on impaired glucose and lipid metabolism and vascular inflammation associated with type 2 diabetes

Abstract: Over the last decades, the incidence of type 2 diabetes (T2D) is increasing substantially. Emerging evidences from epidemiological studies have shown the association between higher intake of soy isoflavones and reduced risk of T2D and its associated health risks. Daidzein, a soy isoflavone, has been found to have a promising therapeutic potential in managing T2D pathophysiology. Fermented soybean is the major source of daidzein; however, it can also be formed via the consumption of its glycosylated moiety, dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 77 publications
(104 reference statements)
1
50
0
1
Order By: Relevance
“…Daidzein belongs to the isoflavone subclass of flavonoids, and is present predominantly in the form of glucosides in various plants, including red clover, alfalfa, soybean, and some legumes [117]. Previous studies suggest that daidzein exerts anti-diabetic effects by improving glucose and lipid metabolism, and downregulating blood glucose, total cholesterol levels, and improving glucose uptake via GLUT4 translocation, as well as AMP-activated protein kinase (AMPK) activation [118,119,120,121]. In in vivo studies, Cheong et al [122] demonstrated that 0.1% daidzein in the diet for 4 weeks suppressed the rise in fasting glucose, lipid levels, and IR and AMPK activation in gastrocnemius muscle compared to the diabetic (Lepr db/db mouse) control group.…”
Section: Flavonoids and Their Effects On T2dmentioning
confidence: 99%
“…Daidzein belongs to the isoflavone subclass of flavonoids, and is present predominantly in the form of glucosides in various plants, including red clover, alfalfa, soybean, and some legumes [117]. Previous studies suggest that daidzein exerts anti-diabetic effects by improving glucose and lipid metabolism, and downregulating blood glucose, total cholesterol levels, and improving glucose uptake via GLUT4 translocation, as well as AMP-activated protein kinase (AMPK) activation [118,119,120,121]. In in vivo studies, Cheong et al [122] demonstrated that 0.1% daidzein in the diet for 4 weeks suppressed the rise in fasting glucose, lipid levels, and IR and AMPK activation in gastrocnemius muscle compared to the diabetic (Lepr db/db mouse) control group.…”
Section: Flavonoids and Their Effects On T2dmentioning
confidence: 99%
“…Isoflavones mainly occur in plants in the form of biologically inactive glycosides (e.g., genistin and daidzein). After ingestion, they are hydrolyzed in the gut by intestinal bacterial β-glucosidases, resulting in the formation of appropriate bioactive aglycones (e.g., genistein and daidzein) [9,10]. Daidzein can be metabolized to dihydrodaidzein and then to equol or O-desmethylangolensin (O-DMA) (Figure 1).…”
Section: Metabolism Of Isoflavonesmentioning
confidence: 99%
“…It has been used traditionally to treat diarrhea, thirst, muscle stiffness, and diabetes for many centuries , and recently has been made commercially available in Western dietary supplements . It abounds in a variety of isoflavones and modern pharmacological studies have confirmed that the isoflavones such as puerarin, daidzein, and genistein have pharmacological activities that regulate hyperglycemia or hyperlipidemia and reduce the risk of type 2 diabetes .…”
Section: Introductionmentioning
confidence: 99%